Market Versus Institutions: Social Mobility Strategies For The Chinese “outsider” Middle Class - Ponzini, Arianna (Asia Pacific Journal of Social Science Research, 2022)
The article examines the social mobility strategies of a widely overlooked social category in contemporary China, i.e. the “outsider” middle class (non-local hukou holders). The argument hereby presented and confirmed by fieldwork research is that, for the outsider middle class, social mobility and advancement are preferably secured through market means, rather than embarking on the institutional path of a hukou conversion. The study avails of a Bourdieusian approach, as well as of Bourdieu’s ideas of class and species of capital, aimed at providing a new categorization framework for the new Chinese middle class. However, although the market plays a greater role in securing social mobility and status for this category, the two paths of market and institutions intersect in correspondence of cultural capital, a crucial capital for the achievement of strong middle-class membership.